PENCEMARAN SITU PANGARENGAN: SUMBER, DAMPAK, PENGENDALIAN DAN PENGELOLAAN - Diana Hendrawan; Melati Ferianita Fachrul; Herika Muhamad Taki; Tazkia Trirastati; Cynthia Nabila (Jurnal Lingkungan dan Kota, 2022)
Situ Pangarengan is located in Cisalak Village, Sukmajaya District, Depok City, and function as a water catchment area. This study aims to identify activities that caouse pollution and damage, analyze the quality and water quality status, determine the pollutant load capacity and provide recommendations for pollution prevention and control. The main cause of pollution in Situ Pangarengan are from residential and other activities. Parameters BOD, COD and phosphate are exceeded the quality standard. The BOD quality standard is 3 mg/L while the BOD content is 2.33 mg/L-11.83 mg/L. The COD quaiity standard is 25 mg/L, the COD content in water ranges from 9.6 mg/L-48 mg/L. The quality standard for phosphate is 0.03 mg/L while the phosphate content in waters ranges from 1.36 mg/L-2.68 mg/L. The water quality status of Situ Pangarengan is 7.53 (moderately polluted). Pollutant load capacity of BOD is 26,787 kg/year, the existing BOD load is 57,770 kg/year. Integrated effort to prevent and pollution control are developing the potential of Situ Pangarengan as a water conservation and tourism area, structuring the lake landscape, providing understanding to the public about the potential of Situ Pangarengan as a supporting ecosystem for urban sustainability, regular dredging, implementing communal WWTPs and eliminating the entry of garbage into the lake, and maintaining the health of the lake.